ANALISIS PENERIMAAN DATA POKOK PENDIDIKAN MENENGAH KABUPATEN KEBUMEN - Nugroho Budhi Ristianto; Suyanto Suyanto; Armadyah Amborowati (Politeknik Sawunggalih Aji, 2018)
Data Basic Secondary Education (Dapodikmen) is a data collection system that integrated education in Indonesia. But in fact, lack of interest and the difficulty of users to adapt to dapodikmen cause a degree of consistency of data collection is uneven. Technology Acceptance Model 3 (TAM 3) is used to determine the factors that influence the level of acceptance of basic data of secondary education. Partial Least Square (PLS) was used for data analysis. Overall results of the analysis can be concluded that the factors that affect the acceptance of the use of the primary data secondary education Kebumen among others Perceived ease of use, perceived usefulnee, bihaviour intention, experience, voluntarines, computer anxiety, computer self-efficacy, subjective norm, result demonstrability and perceived external control. Basic data reception of secondary education (dapodikmen) successfully with a success rate of 81.97%. The researchers suggest, the need for analysis of the different methods to reinforce the results of previous studies. It is also necessary analysis using different theories that enable new discoveries.